UTILIZING PROJECT BASED LEARNING TO IMPROVE WRITING SKILL AND READING COMPREHENSION ACHIEVEMENT OF THE EFL STUDENTS - Sari, Farnia; Hendrety, Yuyun; Tridinanti, Gaya (English Community Journal, 2021)
This study is aimed at finding out whether or not there was any significant difference on reading comprehension achievement between the students who were taught by using Project Based Learning and those who were not and to find out whether or not there was any significant difference on writing skill between the students who were taught by using Project Based Learning and those who were not. This study used quasi experimental study with the nonequivalent research design. The sample was the third semester students of English Study Program at Tridinanti University selected by using purposive sampling technique. Reading comprehension test and essay writing test were used as the instruments. In order to analyze the data, the researchers used paired and independent sample t-test. Having analyzed the data, the findings revealed that both experimental group and control group perform better on the posttest in writing essays. The two groups made progress, the student were mostly in developing category in pretest but they were then in proficient and basic category in posttest. Even though both groups made progress, it can also be stated that students in experimental group performed more progress on posttest in making more structured essay writing than the control group did. Regarding the findings of reading comprehension achievement, it indicates that the students had no significant difference between the students who were taught by using project-based learning and those were not. Although the experimental group had significant improvement in reading comprehension achievement by using Project based learning.